Survey-based Evaluation of a Fish Consumption Information Dissemination Campaign Within an Integrated Health System: Learnings From ChooseYourFish - Jennifer M. Dinh; Meghan M. JaKa; Thomas E. Kottke; Jacob Haapala; Rachael Rivard; Abigail S. Katz; Patricia McCann; Jeanette Y. Ziegenfuss (SAGE Publishing, 2023)
Introduction/Objectives: Safe fish consumption is important for people who are or could become pregnant. A health system in Minnesota partnered with the Minnesota Department of Health to develop and disseminate messages to promote safe fish consumption for this population via the ChooseYourFish initiative. The ChooseYourFish message was delivered through 5 channels: the Healthy Pregnancy Program (HPP) with phone-based coaching, a clinic brochure, in the clinic after visit summary (AVS), direct mailing of the brochure with a letter, and in images on clinic waiting room monitors. Methods: We designed a pragmatic evaluation to understand the likelihood that each channel would result in awareness of the message and increase a recipient's intent to act on the information. We surveyed 1050 women aged 18 to 40 in March-May 2020. Results are reported with descriptive statistics. Results: The survey was completed by 524 respondents (51%). Respondents receiving the ChooseYourFish message through any channel except clinic monitors reported a higher awareness of recommendations about eating fish (42%-56%) than respondents in the no-message comparison group (21%). The after visit summary and Healthy Pregnancy Program channels had more confidence in following recommendations (50%-54%) and showed more intention to eat fish (61%-62%) compared to lower-intensity channels (24%-31% and 19%-32%, respectively). Conclusions: Messages delivered by an often-trusted source (eg, healthcare provider) were more likely to increase confidence and intent. Despite the trend toward online health information, physical brochures still have large reach. Repetition of exposure may be important. Because all communication channels have advantages and drawbacks, using multiple delivery channels is appropriate in communication campaigns.